Environmental Degradation Through (Non)planned and (Il)legal Construction - Pisarić, Milana (Glasnik Advokatske komore Vojvodine, 2025)
In Serbia, the planning, regulation, and use of space, as well as the construction of buildings and the performance of construction works, are regulated by the Law on Planning and Construction, which requires that spatial and urban plans must be in accordance with the Spatial Plan of the Republic of Serbia. The latter serves as the fundamental and highest-level document in this field of planning and, at the same time, in the planning system of the Republic of Serbia, represents a development-planning document with which all strategies and other public policy documents must be aligned. However, the long-term foundations for the organization, arrangement, use, and protection of the territory of the Republic of Serbia—aimed at harmonizing economic and social development with the natural, ecological, and cultural potentials and constraints of its territory—were established only for the period from 2010 to 2020 and not beyond. Consequently, from the perspective of environmental impact, the author examines the strategic-development and general regulatory functions of the Spatial Plan of the Republic of Serbia. In this regard, the paper also analyzes the adequacy of the solutions provided by the Law on Planning and Construction and its accompanying regulations, as well as their compliance with the rules on strategic environmental impact assessment of plans and on environmental impact assessment of projects. This is particularly significant given that the Law explicitly stipulates that the provisions of other laws regulating, in a different manner, the issues covered by this Law do not apply, except for those laws and regulations governing environmental protection.